Transforming Learning Competencies in Thailand’s Primary Education Curriculum from Past to Present - Abdussalam, Nattarika; Sothayapetch, Pavinee; Khuvasanond, Kirati (An Online Journal of Education, 2026)
Elementary education plays a vital role in developing students’ knowledge, skills, and attitude for livelihood and lifelong learning in the 21st century. This article aimed to analyze the evolution of the Thai primary curriculum, examine the shift from content-based to competency-based learning, explore the gaps and challenges in curriculum implementation, and propose practical strategies for teachers. The Thai primary education curriculum has four developmental stages: 1) Teaching for knowledge, focusing primarily on academic content transmission; 2) Learning to think, shifting towards student-centeredness and thinking processes; 3) Learning to apply, introducing five key competencies but still limited by content-heavy indicators; and 4) Learning for real life, moving towards a full competency-based curriculum that integrates learning for living. Reflecting a systematic shift from content-based learning to competency-based learning. To bridge the implementation gap, teachers are encouraged to transform their roles into active learning designers focusing on competency and practice, while employing authentic assessments to monitor progress rather than merely grading. These strategies support students in integrating knowledge, skills, and attributes effectively for sustainable living.